(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Incidence of congenital heart disease is serious and common conditions that have significant impact on morbidity, mortality and healthcare costs in children and adults. The objective of this paper is socio-demographic characteristics, pattern, risk factors and geographical distribution of Congenital Heart Disease (CHD). Methods: This cross-sectional study was conducted throughout the year of 2013 in Dhaka city of Bangladesh. Among the children with confirmed diagnosis of CHD within the age ranging from birth to 18 years, admitted and treated at National Institute of Cardiovascular Disease (NICVD) and National Heart Foundation and Research Center (NHFRC) were included. Result: Out of 168 patients, 64% were living in rural area, 36% were living in urban. The study revealed that 58.9% of male were predominant whereas female was 41.1%. The mean (±SD) age of patients was 4.87(±2.83) years. 71.4% of the children were within 1 to 5 years of age. 36.9% CHD was diagnosed at the age of 1 - 5 years. Finding of the study revealed that there were different types of CHD namely Ventricular Septal Defect (VSD) 35.15%, Atrial Septal Defect (ASD) 27.4%, Patent Ductus Arteriosus (PDA) 13.7%, Coarctation of the aorta 4.8% and Tetralogy of Fallots 19%. In urban area, 37.4% patients had VSD while in rural area, 31.1% patients had ASD. This variation of CHD in relation to living place of the patients was statistically important (χ2 4 = 11.62, p=0.024). In female patients, VSD is more than 58%, however in male patients, ASD is more than 36.4%. This variation of CHD according to sex of the patients was statistically vital (χ2 4 = 27.85, p=0.001). Among the mothers, 39.8% utilized Ant-natal Care (ANC) had VSD while 24.0% having VSD did not utilized ANC. This variation was statistically significant (χ2 4 = 8.235, p=0.04). Among the patients, 41.7% were aged 1-5 years who had VSD while 50.0% were aged 6-10 years who had ASD. This variation was statistically important as it showed (χ2 8 = 43.601, p=0.000) Conclusions: As the most common type of congenital heart diseases are VSD and ASD, the findings of this study will contribute in early detection and proper management of CHD in the contexts to others and thus save lives. JOPSOM 2020; 39(2): 40-44